Belis in the Marriage of the Dawan Community in East Nusa Tenggara - Nur Wahida Yusuf; Yayuk Julyyanti; Nelson Baito Banani (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2022)
This study determines the meaning of belis for the Dawan Tribe in Nonbaun Village. In addition, the study is to find out what are the inhibiting and supporting factors that influence the change in the meaning of belis for the Dawan Tribe in Nonbaun Village, East Nusa Tenggara. A qualitative method is used to conduct the research. The results show belis was interpreted as a tribute to the parents of a woman’s family. Wife’s rights in family can be guaranteed by giving belis from man. The provision of belis can regulate the behavior of the wife in the family. Giving belis can also affect the role of the wife in the household. Wife can work, become heirs, and have rights to their offspring later. Thus, the wife will be free to work at home without feeling awkward, and the wife can give opinions to the family or can act as a representative of the family in traditional events. The Dawan Tribe community places belis as an obligation, so the habit of giving belis is carried out continuously by the local community. This research implies that belis is currently experiencing a shift in meaning, previously containing the value of sacredness, and now that value has shifted to the commercial realm.